2009
DOI: 10.3164/jcbn.08-235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitric Oxide on the Oxygen Metabolism and Growth of E. faecalis

Abstract: Summary Gastro-intestinal mucosal cells have a potent mechanism to eliminate a variety of pathogens using enzymes that generate reactive oxygen species and/or nitric oxide (NO). However, a large number of bacteria survive in the intestine of human subjects. Enterococcus faecalis (E. faecalis) is a Gram-positive bacterium that survives not only in the intestinal lumen but also within macrophages generating NO. It has been reported that E. faecalis generated the superoxide radical (O2 − ). To elucidate the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Additionally, chlorhexidine may induce reactive oxygen species production in the alkaline environment. The production of reactive oxygen species may inhibit E. faecalis growth because of the destruction of the cell wall and the plasma membrane mediated by nitric oxide (30). On the other hand, studies have reported that the antimicrobial activity of chlorhexidine is reduced when it is associated with Ca(OH) 2 (31).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, chlorhexidine may induce reactive oxygen species production in the alkaline environment. The production of reactive oxygen species may inhibit E. faecalis growth because of the destruction of the cell wall and the plasma membrane mediated by nitric oxide (30). On the other hand, studies have reported that the antimicrobial activity of chlorhexidine is reduced when it is associated with Ca(OH) 2 (31).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, both oral bacteria and the infiltrating neutrophils exhibit significant amounts of oxidized proteins. The presence of this oxidative environment in the oral cavity means that not only pathogens, but also commensal bacteria, should have evolved antioxidant defense systems (Park et al, 2004;Sato et al, 2008;Nishikawa et al, 2009). In this study, both H 2 generation and the growth of K. pneumoniae were strongly inhibited by the presence of KCN and FeCl 2 plus H 2 O 2 , a hydroxyl radical generating system.…”
Section: Discussionmentioning
confidence: 81%
“…Antioxidant enzymes, such as superoxide dismutase and catalase, are components of these survival systems. A variety of bacteria living in the oral cavity and gastrointestinal tract, such as Helicobacter pylori, Streptococcus mutans, and Enterococcus faecalis, reduce the toxic effects of NO by generating superoxide radicals (Nagata et al, 1998;Nakamura et al, 2000;Sato et al, 2008;Nishikawa et al, 2009). Since superoxide, NO and peroxynitrite (a reaction product of these two radicals) play important roles in the oxidative damage of a variety of cells, these bacteria should have potent mechanisms for the reduction of oxidative stress caused by reactive species.…”
mentioning
confidence: 99%
“…These findings might suggest an important role of NO in pulpitis and also in dental pulp calcification. In addition, the production of NO might be an important defense mechanism against E. faecalis because the growth of this microorganism is inhibited by NO in a reversible manner (40).…”
Section: Discussionmentioning
confidence: 99%